Factors associated with the diagnosis and complications of COVID-19 among health personnel - Silva, Emanoelle Fernandes; Reis , Renata Karina; Cardoso , Osmar de Oliveira; Freitas , Daniela Reis Joaquim de; Sousa , Roniele Araújo de; Santos, Bárbara Sandra Pinheiro dos; Magalhães , Rosilane de Lima Brito (Revista Prevenção de Infecção e Saúde, 2024)
Introduction: health personnel play a crucial role on the front line against COVID-19, with activities that can increase the risk of infection and complications from the disease. Gaps in tackling the pandemic, especially related to resources, were identified. Aim: to analyze the factors associated with the diagnosis and complications of COVID-19 among health personnel. Desing: this is an analytical cross-sectional study, carried out in Piauí, with health personnel, regardless of serological status for COVID-19. Data collection was carried out in a virtual environment. Mann-Whitney and Pearson’s Chi-square statistical tests were used. The strength of association was measured by Odds Ratio. Results: working in primary health care reduced the chances of diagnosis, while the use of certain prophylaxes, such as hydroxychloroquine, increased the chances. Dexamethasone as prevention increased the complications. Sharing a break room, having multiple jobs, performing endotracheal tube suctioning and nasal/oral swabs increased the chances (statistically significant data). Implications: working directly with patients involves actions that influence the risk of COVID 19, covering health interventions, risk behaviors and factors such as airway manipulation, workload, and work environment. The study emphasizes the urgency of preventive strategies and improved working conditions to protect health personnel.